2006
DOI: 10.2174/092986706776361012
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Fatty Acid Synthase by Polyphenols

Abstract: Recently, animal fatty acid synthase (FAS) is reported as a potential therapeutic target for obesity and cancer. Considerable interest has been developed in identifying novel inhibitors of the enzyme. It is found that tea polyphenols inhibit FAS in both reversible and irreversible manners. Epigallocatechin gallate (EGCG) and epicatechin gallate (ECG) inhibit FAS with IC(50) values of 52 microM and 42 microM mainly by reacting on the beta-ketoacyl reductase (KR) domain of FAS. The inhibitory ability of catechin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(68 citation statements)
references
References 30 publications
2
63
1
2
Order By: Relevance
“…Although the detailed mechanism of the inhibitory effect of polyphenols on FASN was not fully understood, the structure activity association analysis demonstrated that the flavonoids containing two hydroxyl groups in the B ring and 5, 7-hydroxyl groups in the A ring with C-2, 3 double bond were the most potent inhibitors on FASN (31). Patuletin (3,5,7,3',4'-pentahydroxy-6-methoxy-flavone) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Although the detailed mechanism of the inhibitory effect of polyphenols on FASN was not fully understood, the structure activity association analysis demonstrated that the flavonoids containing two hydroxyl groups in the B ring and 5, 7-hydroxyl groups in the A ring with C-2, 3 double bond were the most potent inhibitors on FASN (31). Patuletin (3,5,7,3',4'-pentahydroxy-6-methoxy-flavone) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…However, the most polar solvent ethanol extracted the least inhibitors. It is shown that the FAS inhibitors in Alliums were different from the known natural FAS inhibitors, such as tea-polyphenols and flavonoids (Tian, 2006).In this study, the results showed that the extracts of Alliums strongly inhibited FAS and the mechanism might be related to the interaction with essential sulphydryl groups of FAS. In addition, different inhibitors could exist in various Allium plants.…”
mentioning
confidence: 61%
“…However, the most polar solvent ethanol extracted the least inhibitors. It is shown that the FAS inhibitors in Alliums were different from the known natural FAS inhibitors, such as tea-polyphenols and flavonoids (Tian, 2006).…”
Section: Resultsmentioning
confidence: 91%
“…Epigallocatechin gallate (EGCG) and epicatechin gallate (ECG) inhibit FAS with IC50 values of 52 microM and 42 microM mainly by reacting on the beta-ketoacyl reductase (KR) domain of FAS. The inhibitory ability of catechin gallate (CG) is 15 and 12 folds higher than that of EGCG and ECG (39,40). Nowadays, great progress has been made in the study of fatty acid synthase inhibitor from traditional Chinese medicine.…”
Section: Fatty Acid Synthetase Inhibitormentioning
confidence: 99%